Pengaruh Pengendalian Internal, Transparansi dan Akuntabilitas Terhadap Efektivitas Penggunaan Dana BOS (Studi Kasus pada Sekolah SMPN/MTsN di Kabupaten Aceh Tenggara) - Dewi, Lita Busma (Dinasti Research, 2025)
This study aims to understand the influence of internal control efforts, transparency, and accountability on the effectiveness of BOS fund utilization at SMPN (Senior High School) and MTSN (Islamic Junior High School) in Southeast Aceh Regency. This study applies quantitative methods using the associative method. The population used in this study is the principal, treasurer, and teachers or educational staff directly involved in the utilization of BOS funds. The sample was determined using the Slovin formula with a 1% error rate from a total population of 1,2009 individuals from 29 schools, resulting in 93 respondents who served as samples in this study. Data collection was carried out based on an online questionnaire. Problems found in several schools include a lack of timeliness in reporting, weak internal supervision, and the lack of optimization of transparency and information dissemination efforts in the utilization of BOS funds.The results of the study show that internal control, transparency, and accountability have a significant influence on the effectiveness of the use of BOS funds. This can be proven by the calculated F value at 721.379 and the value of its significance at 0.004, which is less than 0.05, so that an understanding can be obtained that the three related variables have a significant influence on the effectiveness of the use of BOS funds. The better the use of transparent internal control and accountability, the more effective the use of BOS funds in public junior high schools or Islamic junior high schools in Southeast Aceh district.